What doesentrepreneurship data really show? - Zoltán J. Ács; Sameeksha Desai; Leora Klapper (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
We compare two "entrepreneurship" datasets: Global Entrepreneurship Monitor (GEM) captures early-stage entrepreneurship and World Bank Group Entrepreneurship Survey (WBGES) captures business registration. GEM data is higher in developing economies than WBGES data, but this reverses in developed countries. We find differences related to local institutional conditions, after controlling for economic development. A possible explanation is WBGES measures formal entry, whereas GEM measures intent. This can be interpreted as the spread between individuals who could potentially operate businesses in the formal sector and those that actually do. Our findings suggest entrepreneurs in developed countries have greater ease and incentives to incorporate.
Keywords: O17; O50; Y10; 330; Global Entrepreneurship Monitor; World Bank Group Entrepreneurship Survey; entrepreneurial intent; formal business registration; entry; Unternehmer; Unternehmensgründung; Markteintritt; Statistische Methode; Vergleich; Welt